Dendrite‐Free Li Metal Anodes and the Formation of Plating Textures with a High Transference Number Modified Separator. Issue 36 (26th July 2021) - Li, Xuting; Ye, Jiajia; Fu, Zhanghua; Xia, Guang; Chen, Chuanzhong; Hu, Cheng
Abstract: The application of Li metal anodes is currently hindered by the uncontrolled growth of Li dendrites. Herein, the effects of a modified separator with a high Li + transference number ( t + ) on the structure and electrochemical performance of Li metal anodes are reported. Stable and dendrite‐free plating/stripping cycles are achieved under current densities up to 5 mA cm −2 and areal capacities up to 20 mAh cm −2 . The uniformly grown Li grains under the high t + environment also exhibit well‐defined textures (preferred orientations). At a low plating capacity, epitaxial growth takes place on the {100} textures already existing in the rolled Li foils and the uniform Li + flux strengthens this preferred orientation. Increasing the plating capacity to 20 mAh cm −2, the later‐grown textures change to {110} due to the reduced space charges and alleviated transport limits of Li + under the high t + environment, which favor the exposure of the close‐packed {110} planes. Compression‐induced <111> fiber textures are also resolved and the content increases with the plating capacity. Identification of the textures is meaningful for the exploration of advanced epitaxial substrates beyond Cu foils for high‐energy‐density Li metal batteries. LiS pouch cells are finally evaluated for the potential application of the modified separator. Abstract : Dendrite‐free Li metal anodes are enabled by a modified separator with a high Li + transference number based on Fe tetraaminophthalocyanine self‐assembled on rGO. Stable SEIs are formed with high Li + transport kinetics. Well‐defined {100}, {110}, and <111> textures are identified and their evolutions with increasing deposition capacity are discussed. A LiS pouch cell containing the modified separator is demonstrated.